Hierarchically structured NiO/CeO2 nanocatalysts templated by eggshell membranes for methane steam reforming - Wang, Zhitao; Shao, Xin; Hu, Xun; Parkinson, Gordon; Xie, K.; Dong, Dehua; Li, Chun-Zhu (Elsevier BV, 2014)
A template synthesis process has been studied to prepare hierarchically structured NiO/CeO2 nanocatalysts by using eggshell membranes as a template. The templated catalyst is constructed by interwoven ceramic fibres, and the fibres have a nanoporous structure with NiO nanoparticles supported on a CeO2scaffold. The effects of immersion time and calcination temperature on catalyst microstructure were investigated using SEM, XRD, TGA and TPR techniques. The catalyst prepared with an immersion time of 3 h has a robust structure that is able to resist internal thermal stresses caused by cooling down after calcination. Calcination temperature greatly affected the performance of steam reforming via catalyst microstructure. Both particle size and the interaction between NiO and CeO2 determined the reforming performance. The catalyst calcined at 950°C achieved the highest and most stable methane conversion owing to the optimized microstructure. The strong NiO–CeO2 interaction is critical to achieve coking-resistance. The three-dimensional structure of the fibrous catalyst ensured the high thermal stability of the nanocatalyst in terms of high resistance to catalyst sintering.